Ultimate strength assessment of intact and pitted platings under biaxial compression. (1st February 2020) - Piscopo, V.; Scamardella, A.
Highlights: Ultimate strength assessment of uncorroded and pitted platings under biaxial compression. Incidence of pitting (DOP) and corrosion (DOC) degrees on the ultimate strength of pitted platings. Practical design formulas for uncorroded and pitted platings under biaxial compression. Non-linear finite element analysis by Ansys Mechanical APDL. Abstract: The paper focuses on the ultimate strength assessment of intact and pitted platings under uniaxial and biaxial compression, in order to provide a unified formulation, which can be embodied both in the design phase of new ships and in the assessment procedures of aged structures. In this respect, a large number of FE simulations, performed by Ansys Mechanical APDL, is preliminarily carried out, in order to derive, by best-fit interpolation, new design formulas for intact platings under uniaxial and biaxial compression. Subsequently, a two-step procedure for pitted platings is outlined and checked against a new series of FE results, based on random generation of localized corrosion wastage over the plate panel for several combinations of pitting and corrosion intensity degrees, in order to investigate the effectiveness of the proposed procedure. Finally, current formulas are compared with additional FE results available in literature and with the design equations embodied in the Harmonized Common Structural Rules for Bulk Carriers and Oil Tankers. Based on current results, the new equations for uniaxial and biaxial compression, as well as the two-step procedure for pitting corrosion wastage, reveal to be effective for practical design purposes.